Identification and Qualitative Analysis of Liquid Effluents in the Spatial Planning Stage of a New Nuclear Power Plant Project - Fackovič, Pia; Debelak, Klemen; Zupančič, Kaja; Žagar, Tomaž (Journal of Energy Technology, 2026)
Planned JEK2 will generate liquid effluents during normal operation, categorized as radioactive and non-radioactive. Radioactive releases will mainly consist of tritium, while other radionuclides will be present only in trace amounts, all below the authorized limits. Non-radioactive effluents, originating from cooling and service water systems, will be treated by filtration, pH adjustment, and biocide neutralization. Thermal load of non-radioactive emissions to the Sava will be minimal to negligible levels, as the cooling tower serves as the heat sink. All effluents from JEK2 will be managed by design through defence in depth: multi-barrier treatment and holdup, controlled storage and release, and comprehensive monitoring under the ALARA principle to keep impacts low and within strict regulatory limits